PD-1 and PD-L1 regulate cellular immunity in canine visceral leishmaniasis - Oliveira Silva, Kathlenn Liezbeth [UNESP]; Marin Chiku, Vanessa [UNESP]; Luvizotto Venturin, Gabriela [UNESP]; Correa Leal, Aline Aparecida [UNESP]; de Almeida, Breno Fernando [UNESP]; De Rezende Eugenio, Flavia [UNESP]; Dos Santos, Paulo Sergio Patto [UNESP]; Fabrino Machado, Gisele [UNESP]; De Lima, Valeria Marçal Felix [UNESP] (Elsevier, 2019)
PD-1 is a negative costimulator of chronic infectious diseases In this study, we investigated the expression of PD-1 and its ligands in the spleen of dogs with visceral leishmaniasis and lymphoproliferative response to soluble antigen, in lymph node cells in the presence or absence of antibodies blocking PD-1 and its ligands. Our results showed expression of PD-1 and its ligands is higher after L. infantum infection and in the spleen of infected dogs, PD-1 blockage was able to restore the antigen-dependent lymphoproliferative response and regulated production of the cytokines IL-4 and IL-10 and NO production. We concluded that L. infantum infection modulates PD-1 and its ligands expression in canine VL and that blockage of PD-1 restores the immune response. Thus, blockage of PD-1 is a target for therapeutic drug development.
Keywords: Canine; Cytokine; Lymphoproliferation; Nitric oxide; PD-1; Visceral leishmaniasis